Genesis and Prospects of Higher Insurance Education Development in Russia - Y. V. Gryzenkova; E. V. Zlobin; A. A. Tsyganov (Высшее образование в России)
The article discusses the history and stages of development of insurance education in Russia in comparison with the development of the insurance market in 1990–2020, determines the prospects and conditions for development of insurance education. The internal and external factors that influenced the direction and rate of the market of educational services development in the field of insurance are highlighted, the reasons for the creation and liquidation of specialized departments in Russian universities are analyzed. Based on the analysis of the Russian insurance market in 1990-2020, an understanding of the real and reported indicators of the insurance market is being formed, the differences in which caused at the first stage the creation of a significant number of insurance departments in Russian universities, not supported by a real need for specialists, and then the liquidation of the departments with the loss of the already established competencies for training insurance specialists. In the late 2010s, the modernization processes in the requirements for insurance organizations took place, the financial stability and solvency standards were being raised, mandatory actuarial valuation and new forms of financial reporting were being introduced that required specialized knowledge, basic and professional standards were being developed and adopted with the participation of self-regulatory organizations of insurers. All of that actualized the activities of specialized insurance departments based on the integration of professional requirements fixed in professional and basic standards, and educational standards, which should allow the implementation of economically successful undergraduate and master’s programs.The history of insurance departments in modern Russia may be of interest to researchers of the history of education in modern Russia, the origins and causes of the current state of the educational services market, periods of growth and decline in the number of active players. Based on the analysis of archival and current insurance development strategies, the article highlights the adopted basic and professional standards, prospects for the development of insurance departments, gives recommendations for interaction with professional participants of the insurance market. The revealed trends are also typical for other highly professional departments.